Plant Parasitic Nematodes in Agricultural Ecosystem of Indonesia - Chaerani Chaerani (Universitas Gadjah Mada, 2022)
The plant-parasitic nematode (PPN) is often not recognized as important limiting crop production in Indonesia. This is largely caused by non-specific and non-dramatic above-ground plant disease symptoms, their microscopic nature, and partly caused by inadequate demonstration of the economic importance of this hidden pathogen. However, change in agricultural practices to meet the ever-increasing food demand along with global climate change may increase the risk of PPNs on crop productivity in the future. This paper reviews PPN inventory in Indonesia during the last three decades. Thirty-three genera of PPNs were found to associate with 25 host plants. Some genera were present at the densities that are considered as damaging levels in other countries. Results among surveys are difficult to compare because of differences in crop cultivar surveyed, cultivation practices, sampling unit and method, and nematode extraction techniques. Lack of field supporting data did not permit a valid assessment of nematode risk on a particular crop. The first record of several quarantined species has been reported, but not all of them have been validated molecularly. Challenges and opportunities to improve the future field survey are presented in this paper.